Implementing ICT in Rural Community Schools: Challenges and Strategies for Effective Integration - Sigdel, Janak; Joshi, Bishow Raj (Educational Journal, 2026)
This article explores the challenges of integrating information and communication technology (ICT) in rural community schools in Nepal. It also discusses the obstacles and examines the strategies teachers employ to overcome these obstacles in the language classrooms. Employing a phenomenological qualitative research design, semi-structured interviews were conducted among twenty teachers across five rural community schools to explore the challenges of ICT integration. The gathered data were thematically analyzed to identify the key obstacles and strategies to overcome them. Findings reveal that teachers were struggling to integrate ICT in their classroom teaching due to the challenges of inadequate ICT resources, insufficient ICT training, lack of technical support and poor internet connection and inconsistent electricity supply. Despite these obstacles, teachers implement various mitigation strategies, such as using mobile data during electricity cuts, applying ICT training knowledge and skills, and taking support from local government. This study suggests the practical approaches for enhancing ICT integration in under-resourced rural settings and provides mitigating ways for overcoming these challenges.